Analisis Kebutuhan Pengembangan Booklet Terintegrasi Nilai Preventif Kesehatan Pada Materi Sistem Pernapasa Manusia Untuk Peserta Didik Fase F - Nasution, Ika Tiara (LP2M IAIN Ambon, 2025)
This research proposes a needs analysis of teachers and students as a reference for the development of booklets integrated with preventive values at SMAN 1 Barumun. The type of research conducted is quantitative descriptive research, while data collection techniques are in the form of interview sheets and questionnaires. The subjects of this study were 1 Biology teacher and students of class XI Phase F which amounted to 31 students. The result is that the booklet can attract students to learn and practice the steps of how to maintain a healthy body through the preventive value integrated in the learning media. From this, students stated that they needed additional interesting learning media to support the learning process. These results indicate the need to develop learning media in the form of booklets integrated with preventive health values on human respiratory system material.